La prisión: mecanismos de poder, suplicio y exclusión. El fracaso del sistema penitenciario en Los hijos del orden de Luis Urteaga Cabrera - Olivares Acate, César Humberto (2019)
This article present the way as the prison is represented inside narrative’s development of the facts in the novel Los hijos del orden, like an instrument of torture and exclusión of the subaltern subject. In this sense, the jail become to represent a clear way of segregation of the oppressed clases which repression is overloaded with discriminatories and racist backgrounds. In addition to the plot, it explains the way in which the modern reforms of the penitentiary system fail down when they try to correct the criminal conducts of the protagonists of the novel studied.